Isolation, Purification & Characterization Of Asparginase From Eschereshia Coli . - SATPAL SINGH BISHT; B.PRAVEEN; AMRITA PANDA; KAUSTAVA PANDA; SANTOSH BEHERA (International Journal of Pharma and Bio Sciences, 2011)
Asparginase is an enzyme that catalyzes the hydrolysis of aspargines to aspartic acid. It is marketed under the brand name Elspar to treat acute lymphoblastic leukemia. Eschereshia coli, capable of producing asparginase was isolated from local habitats and screened for its production on corn steep liquor. The extracted enzyme was purified by ammonium sulphate precipitation,dialysis and anion exchange chromatography and was estimated quantitatively by Lowry method. Effect of temperature and pH were also studied on the purified enzyme and the enzyme activity was found to be optimum at pH 5 and 37 ° C temperature.